Clinical Practice Guidelines for Prenatal Aneuploidy Screening and Diagnostic Testing from Korean Society of Maternal-Fetal Medicine: (2) Invasive Diagnostic Testing for Fetal Chromosomal Abnormalities - Lee, Ji Yeon (J Korean Med Sci, 2021)
The Korean Society of Maternal Fetal Medicine proposed the first Korean guideline on prenatal aneuploidy screening and diagnostic testing, in April 2019. The clinical practice guideline (CPG) was developed for Korean women using an adaptation process based on good-quality practice guidelines, previously developed in other countries, on prenatal screening and invasive diagnostic testing for fetal chromosome abnormalities. We reviewed current guidelines and developed a Korean CPG on invasive diagnostic testing for fetal chromosome abnormalities according to the adaptation process. Recommendations for selected 11 key questions are: 1) Considering the increased risk of fetal loss in invasive prenatal diagnostic testing for fetal genetic disorders, it is not recommended for all pregnant women aged over 35 years. 2) Because early amniocentesis performed before 14 weeks of pregnancy increases the risk of fetal loss and malformation, chorionic villus sampling (CVS) is recommended for pregnant women who will undergo invasive prenatal diagnostic testing for fetal genetic disorders in the first trimester of pregnancy. However, CVS before 9 weeks of pregnancy also increases the risk of fetal loss and deformity. Thus, CVS is recommended after 9 weeks of pregnancy. 3) Amniocentesis is recommended to distinguish true fetal mosaicism from confined placental mosaicism. 4) Anti-immunoglobulin should be administered within 72 hours after the invasive diagnostic testing. 5) Since there is a high risk of vertical transmission, an invasive prenatal diagnostic testing is recommended according to the clinician's discretion with consideration of the condition of the pregnant woman. 6) The use of antibiotics is not recommended before or after an invasive diagnostic testing. 7) The chromosomal microarray test as an alternative to the conventional cytogenetic test is not recommended for all pregnant women who will undergo an invasive diagnostic testing. 8) Amniocentesis before 14 weeks of gestation is not recommended because it increases the risk of fetal loss and malformation. 9) CVS before 9 weeks of gestation is not recommended because it increases the risk of fetal loss and malformation. 10) Although the risk of fetal loss associated with invasive prenatal diagnostic testing (amniocentesis and CVS) may vary based on the proficiency of the operator, the risk of fetal loss due to invasive prenatal diagnostic testing is higher in twin pregnancies than in singleton pregnancies. 11) When a monochorionic twin is identified in early pregnancy and the growth and structure of both fetuses are consistent, an invasive prenatal diagnostic testing can be performed on one fetus alone. However, an invasive prenatal diagnostic testing is recommended for each fetus in cases of pregnancy conceived via in vitro fertilization, or in cases in which the growth of both fetuses differs, or in those in which at least one fetus has a structural abnormality. The guidelines were established and approved by the Korean Academy of Medical Sciences. This guideline is revised and presented every 5 years.